Contribution of NDM and OXA-type carbapenemases to carbapenem resistance in clinical Acinetobacter baumannii from Nigeria. Issue 9 (1st September 2020) - Ogbolu, David O.; Alli, Oyebode A. Terry; Oluremi, Adeolu S.; Ogunjimi, Y. Temilola; Ojebode, D. Iyanu; Dada, Veronica; Alaka, Olubunmi O.; Foster-Nyarko, Ebenezer; Webber, Mark A.
Abstract: Objective: Acinetobacter baumannii infections are rarely diagnosed in many hospitals in Nigeria due to a lack of capacity for the identification of the organism in spite of the clinical significance of this opportunistic nosocomial organism. We assembled a panel of presumptive isolates of A. baumannii from tertiary hospitals in Nigeria and analysed mechanisms of resistance phenotypically and by whole genome sequencing. Materials and methods: Twenty-one clinical isolates of A. baumannii identified using standard microbiological tests were tested for susceptibility to a panel of antibiotics by the agar dilution method, and production of ESBLs using phenotypic tests. Whole genome sequencing and comparative genomic analysis were used to determine the antimicrobial resistance genes, strain types, phylogenetic relationships and genetic context of resistance genes. Results: The MIC50 and MIC90 of most antibiotics were very high with no difference between MIC50 and MIC90 values apart for amikacin, meropenem and colistin where MIC50 and MIC90 ranged between 1–4 µg/ml and 64–>64 µg/ml, respectively. Multiple resistance genes were detected in most of the isolates including bla NDM-1, various bla OXA-51 family alleles and bla OXA-23 . Interestingly, bla NDM-1 carriage did not always result in phenotypic carbapenem resistance. Whole genome alignments typing showed strains belonged to three major clades. Strains within these clades had different resistance genes and resistance patterns. Conclusions: This report shows a high level of resistance to important antibiotics and carbapenem resistance in A. baumannii in Nigeria. We hope this work will serve as a reference for future study in the sub-Saharan region of Africa.